Dissolved and Particulate Beryllium Isotopes in the Pearl River Estuary: Their Geochemical Behavior in Estuarine Water and Potential Contributions From Anthropogenic Sources - Kong, Weiyuan; Zhou, Liping; Aumaître, Georges; Bourlès, Didier; Keddadouche, Karim (Frontiers in Marine Science, 2021)
The ratio of cosmogenic 10Be and its stable isotope 9Be has been used as a proxy of long-term continental weathering fluxes and denudation rates, but transport processes of these isotopes from river water to estuarine water and seawater, as well as interference of potential anthropogenic source of 9Be on natural 10Be/9Be around populated estuaries are not well constrained. Here, we present results of 10Be and 9Be concentrations of dissolved and reactive particulate phase in the Pearl River Estuary (PRE) and its eight major outlets. The concentrations of Cu, Cd, and Pb are also measured, allowing us to assess their contamination levels and anthropogenic source together with 9Be by the geo-accumulation index (Igeo-reac) and enrichment factor (EF). A wide distribution pattern of dissolved 10Be (137-1194 at/gwater) and 9Be (0.781-8.31×10-12 g/gwater) among these outlets is observed. The distribution coefficients (Kd) of both isotopes between sediment and water are in the order of 105, and on average only 5% of 10Be exists as dissolved form. Compared with total meteoric 10Be deposited on the river basin, 23% of the meteoric 10Be is retained while 38% of 10Be finally escape the estuary and is transported into coastal seawater. Despite the high contamination levels of Cu and Cd, the lower Igeo-reac and EF values of 9Be indicate that 9Be is hardly polluted by anthropogenic source. Thus, the 10Be/9Be in the PRE area is mainly associated with natural processes instead of human activities.